The Influence of Salary, Work Environment, and Working Hours on Employee Turnover Intention at Bintang Pulubala Farm - Jusuf, Fina Angelina; Suyanto, Moh. Afan; Usman Rasyid, Ayub; Novriansyah, Moh. Arif (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze the effect of salary, work environment, and working hours on employee turnover intention at Bintang Pulubala Farm. Turnover intention is an essential indicator in human resource management that can affect the stability of a company's workforce. This research uses a quantitative method with data collection techniques through questionnaires distributed to 93 permanent employees at Bintang Pulubala Farm. The data obtained were analyzed using multiple linear regression analysis with classical assumption tests to ensure data validity and reliability. The independent variables in this study are salary, work environment, and working hours, while the turnover intention is the dependent variable. The results showed that salary had a negative and significant effect on turnover intention, which means that the higher the salary, the lower the employee's desire to change jobs. The work environment also negatively and significantly affects turnover intention, indicating that a conducive work environment can reduce employee intentions to leave. Meanwhile, working hours have a positive and significant effect on turnover intention, which means that the higher the workload, the more likely employees are to look for other jobs. This study concludes that salary and work environment factors can be the main strategies for reducing turnover intention. At the same time, more flexible working hour management can be a solution to increase employee retention. Therefore, company management is advised to improve employee welfare through more competitive wage policies and a better work environment to reduce turnover intention.